Burkina Faso : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2006)
Executive Directors are of the view that Burkina Faso's implementation of its Poverty Reduction Strategy (PRS) has allowed solid progress, and the broad direction of policies and programs seems appropriate for achieving PRS objectives. The emphasis on governance and anticorruption efforts, particularly in the area of public finance management, is commended. Strengthening the link with the Millennium Development Goals, emphasizing trade issues and policies for growth and economic diversification, and promoting an efficient delivery of education and health services are required.